2013
DOI: 10.1371/journal.pone.0059436
|View full text |Cite
|
Sign up to set email alerts
|

LRRC6 Mutation Causes Primary Ciliary Dyskinesia with Dynein Arm Defects

Abstract: Despite recent progress in defining the ciliome, the genetic basis for many cases of primary ciliary dyskinesia (PCD) remains elusive. We evaluated five children from two unrelated, consanguineous Palestinian families who had PCD with typical clinical features, reduced nasal nitric oxide concentrations, and absent dynein arms. Linkage analyses revealed a single common homozygous region on chromosome 8 and one candidate was conserved in organisms with motile cilia. Sequencing revealed a single novel mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 52 publications
3
70
0
2
Order By: Relevance
“…We further show that Reptin directly interact with Lrrc6/ Seahorse, a protein very recently linked to PCD (18,45). Consistent with this physical interaction, mutants of reptin and lrrc6/seahorse were identified in the same genetic screen in zebrafish and both show similar body curvature and kidney cyst formation (22,23).…”
Section: Discussionsupporting
confidence: 75%
“…We further show that Reptin directly interact with Lrrc6/ Seahorse, a protein very recently linked to PCD (18,45). Consistent with this physical interaction, mutants of reptin and lrrc6/seahorse were identified in the same genetic screen in zebrafish and both show similar body curvature and kidney cyst formation (22,23).…”
Section: Discussionsupporting
confidence: 75%
“…Next, we obtained a previously described insertional mutant, ift172 hi2211tg (Sun et al, 2004), and performed a complementation test; we confirmed that ccn1.9 pd1085 is a mutated allele of ift172. Similarly,dx33.9 pd1087 mapped to an interval containing lrrc6, which encodes a dynein arm ciliary component (Horani et al, 2013), that bears a T-to-G nonsense…”
Section: Implementation Of the Wes Methods For The Identification Of Mmentioning
confidence: 99%
“…35,60,61 Gene-specific shRNA sequences subcloned into the pLKO.1 transfer plasmid 62 were from the RNAi Consortium collection including a control nontargeted sequence (SHC016), 2 ATG5-specific sequences (#1, TRCN0000330392; #2, TRCN0000330394) and one ATG14-specific sequence (TRCN0000010211), all available from Sigma-Aldrich. Recombinant lentiviruses were produced by co-transfection of the specific pLKO.1 plasmid that includes a cassette for puromycin resistance with plasmids containing packaging (pHR'8.2DR) and envelope (pCMV-VSV-G) sequences in HEK293T cells using FuGENE 6 (Promega, E2691) as described.…”
Section: Rna Interferencementioning
confidence: 99%